2020
DOI: 10.1371/journal.pone.0230977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-Ergothioneine on the metabolic plasma profile of the RUPP rat model of pre-eclampsia

Abstract: Introduction Pre-eclampsia is a major cause of maternal and fetal mortality and morbidity worldwide. Its pathophysiology remains unclear, but mitochondrial dysfunction and oxidative stress have been implicated. L-Ergothioneine is a naturally occurring, water-soluble betaine, that has demonstrated antioxidant properties. Using the reduced uterine perfusion pressure (RUPP) rat model of pre-eclampsia, this study aimed to define the plasma metabolic profile following treatment with L-Ergothioneine. Methods The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…A nutraceutical mitochondria-targeted antioxidant, L-ergothioneine (ERG), has also demonstrated potential therapeutic effects, particularly in PE ( 202 ). ERG is a water-soluble amino acid derived from histidine, which accumulates preferentially in high oxidative stress organs through the action of a specific organic cation transporter novel type 1 (OCTN1) ( 203 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…A nutraceutical mitochondria-targeted antioxidant, L-ergothioneine (ERG), has also demonstrated potential therapeutic effects, particularly in PE ( 202 ). ERG is a water-soluble amino acid derived from histidine, which accumulates preferentially in high oxidative stress organs through the action of a specific organic cation transporter novel type 1 (OCTN1) ( 203 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Moreover, studies have suggested that ET is preferentially accumulated in tissues predisposed to oxidative stress and inflammation and may even be concentrated at sites of tissue injury by cellular modulation of the levels of OCTN1 [ 24 , 32 , 56 , 57 ]. These unique capabilities of ET, which have been reported in a wide range of studies in cells, animal models, and also population studies, suggest that the cytoprotective abilities of ET may be helpful against disorders such as dementia [ 58 , 59 , 60 ], depression [ 61 ], atherosclerosis [ 45 , 46 ], cardiovascular disorders [ 46 , 62 , 63 , 64 ], nonalcoholic fatty liver disease [ 56 ], preeclampsia [ 65 , 66 ], ischemia-reperfusion injury [ 39 , 50 , 67 ], and, especially relevant in this case, ARDS [ 68 ]. This list is by no means exhaustive, with new applications for ET constantly being identified even in other areas of human health, such as improving the efficacy of cancer vaccines [ 69 ] and protection against chemotherapy-induced peripheral neuropathy [ 70 ].…”
Section: Biology Of Ergothioneinementioning
confidence: 99%
“…Studies have also suggested that ET is protective in preeclampsia, a hypertensive disorder during pregnancy that results in placental ischemia, by protecting against reperfusion-induced oxidative stress and inflammation, preserving mitochondrial function, and reducing hypertension in a reduced uterine perfusion pressure rat model of preeclampsia [ 65 , 66 , 154 ]. Conversely, mice deficient in OCTN1 (whose tissues are completely devoid of ET) are more susceptible to intestinal ischemia and reperfusion injury, with higher inflammatory markers and mortality compared with wild-type animals [ 101 ].…”
Section: How Might Ergothioneine Be Beneficial In Alleviating Covimentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant rats were randomised to the Sham or RUPP procedure. At gestational day (GD) 14, the RUPP operation was performed as previously described [29,30]. Brie y, silver clips were applied to the aorta above the iliac bifurcation (0.203 mm ID) and both the right and left uterine arcades (0.100 mm ID) to reduce the blood ow to the uterus by ~ 40%.…”
Section: Experimental Animalsmentioning
confidence: 99%